Income changes do not influence political participation: Evidence from comparative panel data - Sebastian Jungkunz; Paul Marx (Deutsches Institut für Wirtschaftsforschung (DIW), 2021)
The income gradient in political participation is a widely accepted stylized fact. This article asks how income effects on political involvement unfold over time. Using nine panel datasets from six countries, it analyzes whether income changes have short-term effects on political involvement, whether effects vary across the life-cycle, and whether parental income has an independent influence. Irrespective of indicator, specification, and method (hybrid models, inclusion of lags and leads, error-correction models), we find neither significant short-term effects of income changes nor life-cycle variation in these effects. However, parental income does seem to affect political socialization. Descriptive evidence and latent-growth-curve modeling based on household panels show that participatory inequality by parental income is already large before voting age. Poorer voters do not catch up with their richer peers in their twenties. This implies an urgent need for research on (political) inequality in youth and childhood.
Keywords: C23; D31; D72; D91; P16; Z13; 330; Participation; political inequality; panel data; socialization; income